Instructional Design of Online Training for ECE Educators: A Project-Based and Andragogical Approach - Tepati Kewajiban; Susy Puspitasari; Suryo Prabowo; Ahmad Syaikhu; Apri Kasman (Jurnal Altifani Penelitian dan Pengabdian kepada Masyarakat, 2025)
Enhancing Early Childhood Education (ECE) educators' digital media creation skills is crucial for innovative teaching, yet effective, practical professional development often remains a significant challenge. This article presents a detailed instructional design for an online training program, developed as an outcome of a community service initiative with a private ECE institution in Indonesia. This initiative involved its eleven educators, who possessed varied initial digital competencies, and aimed to address their specific needs. The design process employed a systematic needs analysis, integrating project-based learning and established andragogical principles to ensure relevance and practical application for adult learners. The resulting online program features a three-tiered competency structure (Beginner, Intermediate, Advanced), where each level culminates in authentic media creation projects, fostering skills through learner-centered, reflective, and collaborative activities. This theoretically-grounded instructional design offers an adaptable model anticipated to significantly improve ECE educators' digital competencies and creative capacities, thereby enriching children’s learning experiences.